An Analysis of Transitivity Shift of Barack Obama's Translated Speeches - Nufus, Chayatun (2014)
The research is entitled AN ANALYSIS OF TRANSITIVITY SHIFT OF BARACK OBAMA'S TRANSLATED SPEECHES. The aims of the research are to investigate the transitivity shift in the speeches and to analyze the possible meanings behind the shifts that occur. The research employed a qualitative method which attempts to define, classify, analyze, and describe the collected data. The researcher used transitivity of Halliday (1985) and transitivity shift of Calzada Perez (2007) as the tools of analysis. It can be seen that the transitivity shift occured in the speeches. In the first speech, it can be seen that modality shift is the most frequent shift. It indicates that the translator may ignore the author's intention to avoid responsibility to the truth of a statement. In the second and third speeches, it can be seen that expansion is the most frequent shift. It is evident that the translators used more active clauses in the target text and use more than one processes in the clauses of the target text. The target texts are more understandable because it is explained clearer. From the findings about transitivity shift, it was found that the transitivity shifts happened in order to adapt the target language so that the translated text can be understood by the target audiences and it should be natural. In addition, it may be that the translators are unaware of his or her decision on making the shift. The translator may do it without any intentions. However, almost any decision in translation is consciously or unconsciously guided by translator's background (point of view, ideology or cultural values). In conclusion, the translators tend to leave the reader in peace as much as possible by bringing the text as close as possible to the target text or home to the reader.